Stromal-mediated protection of tyrosine kinase inhibitor-treated BCR-ABL-expressing leukemia cells - Weisberg, Ellen (2008)
Clinical studies of patients with chronic myeloid leukemia (CML) revealed that a common pattern of response is a dramatic fall in the circulating population of blast cells, with a minimal or delayed decrease in marrow blasts, suggesting a protective environment. These observations suggest that a greater understanding of the interaction of stromal cells with leukemic cells is essential. Here, we present an in vivo system for monitoring relative tumor accumulation in leukemic mice and residual disease in leukemic mice treated with a tyrosine kinase inhibitor, and an in vitro system for identifying integral factors involved in stromal-mediated cytoprotection. Using the in vivo model, we observed high tumor burden/residual disease in tissues characterized as significant sources of hematopoiesis-promoting stroma, with bone marrow stroma most frequently showing the highest accumulation of leukemia in untreated and nilotinib-treated mice, as well as partial protection of leukemic cells from the inhibitory effects of nilotinib. These studies, which showed a pattern of leukemia distribution consistent with what is observed in imatinib- and nilotinib-treated CML patients, were followed by a more in-depth analysis of stroma-leukemia cell interactions that lead to protection of leukemia cells from nilotinib-induced cytotoxicity. For the latter, we used the human BCR-ABL-positive cell line, KU812F, and the human bone marrow stroma cell line, HS-5, to more closely approximate the bone marrow-associated cytoprotection observed in drug-treated leukemia patients. This in vitro system helped to elucidate stromal-secreted viability factors that may play a role in stromal-mediated cytoprotection of tyrosine kinase inhibitor-treated leukemia cells.